Assessment of the effect of FRCM materials on the behaviour of masonry walls by means of FE models. (1st April 2019) - Lignola, G.P.; Bilotta, A.; Ceroni, F.
Highlights: Several studies are devoted to the use of Fiber Reinforced Cementitious Matrix. FRCM are used for strengthening and seismic retrofitting of masonry structures. In this paper several numerical analyses were carried by means of a FE Model. Abstract: Several experimental tests recently performed on tuff or clay brick masonry elements (i.e. walls and arches) demonstrated the benefits of Fiber Reinforced Cementitious Matrix (FRCM) systems used as externally bonded reinforcement for strengthening and seismic retrofitting of masonry structures. Tensile tests on coupons made of different FRCM materials allowed defining constitutive laws in tension, which are characterized by a post-cracking behaviour with more or less effective tension stiffening effect. This paper is focussed on the assessment of the influence of the mechanical properties of both the masonry substrate and the FRCM systems on the overall behaviour of strengthened masonry walls subjected to diagonal compression. To this aim, several numerical analyses were carried out for simulating diagonal compression tests by means of a bi-dimensional Finite Element Model. A non-linear behaviour was assumed for both masonry substrates and FRCM reinforcements. For the latter ones, a perfect bond condition was assumed and the tension stiffening effect of the mortar was taken into account in the tensile behaviour of the FRCM reinforcement based on experimental results previously carried out by the Authors.